Supply disruptions and protection motivation: Why some managers act proactively (and others don't). Issue 1 (31st October 2021) - Bode, Christoph; Macdonald, John R.; Merath, Maximilian
Abstract: Supply (chain) disruptions present considerable managerial challenges with potentially severe consequences. To protect their firms, managers often must decide whether or not to take proactive measures. Protection motivation theory suggests that individuals' intention to respond to a threat proactively results from their cognitive appraisal (situational interpretation) processes. These processes evaluate the characteristics of potential coping responses (e.g., its effectiveness in averting the threat) and the threat itself (e.g., its severity). Building on this framework, this study presents an analysis of what drives managers to, or deters them from, proactively responding to the threat of a disruption. The results from a discrete choice experiment suggest that decision makers have a strong subconscious focus on cost‐related aspects of a specific proactive action, all the while consciously prioritizing the efficacy (effectiveness) of the action over its costs. Moreover, decision makers' perceptions of the relative importance of proactive action attributes deviate considerably from their actual choice behavior. This study investigates additional behavioral aspects of supply chain risk management such as a proactive personality, risk attitude, control appraisal, and experience, many of which have significant effects on the relative importance of certain proactive action attributes. The improved understanding has three relevant messages for managerial practice, which are related to the perception–action gap, the importance of self‐assessment and self‐awareness, and training.